2010
DOI: 10.1002/meet.14504701228
|View full text |Cite
|
Sign up to set email alerts
|

Beyond everyday life: Information seeking behavior in deeply meaningful and profoundly personal contexts

Abstract: Information seeking behavior research is traditionally partitioned into two realms of life experiences: 1) work or job related; 2) everyday life information seeking (Savolainen, 2010). These two spheres encompass a significant share if not majority of life's time and effort at the universal level. This paper examines information seeking behavior within two specific contexts far outside the realm of everyday life. Characterized as deeply meaningful and intensely personal with life-long impacts, these contexts m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Over the past few decades, studies in the area of ISB have advanced, moving beyond a resource‐focused to a person‐centric perspective (Clemens & Cushing, ). Numerous models have been developed to describe and explain complex relationships between a person's perceived information needs, cultural and situational contexts, information resources, systems, and intermediaries (Ingwersen & Järvelin, ).…”
Section: Literature Surveymentioning
confidence: 99%
“…Over the past few decades, studies in the area of ISB have advanced, moving beyond a resource‐focused to a person‐centric perspective (Clemens & Cushing, ). Numerous models have been developed to describe and explain complex relationships between a person's perceived information needs, cultural and situational contexts, information resources, systems, and intermediaries (Ingwersen & Järvelin, ).…”
Section: Literature Surveymentioning
confidence: 99%
“…As Ross says, readers are open to their environment for new reading possibilities and connections, and some reading material contributed to one's sense of identity. On the note of identity, Clemens and Cushing () found that information sought in emotional and personal situations comes to be part of one's identity. As their participant Kate said, “I'm searching for answers in my own identity” (Clemens & Cushing, , p. 9).…”
Section: Discussionmentioning
confidence: 99%
“…On the note of identity, Clemens and Cushing () found that information sought in emotional and personal situations comes to be part of one's identity. As their participant Kate said, “I'm searching for answers in my own identity” (Clemens & Cushing, , p. 9). Considered from a more general philosophical perspective, this demonstrates Floridi's () assertion that you are your information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations